PEMILIHAN PRIORITAS PROGRAM KERJA DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS PADA PT. GARUDA INDONESIA CARGO - Dimas Novrisal; Farah Almira; Eva Febrianty (Jurnal Logistik Indonesia, 2019)
Company is required to compete and being innovated to carry out work program strategies in order to improve the service quality while deliver goods to consumers. Due to limited resources, companies need to prioritize work programs based on existing criteria. The purpose of this study is the selection of work program priorities using the analytical hierarchy process method at PT. Garuda Indonesia Cargo. This research begins with determining the criteria and alternatives that are carried out for making questionnaires, then distributing questionnaires to get priority criteria and alternatives using the AHP method. The results of data processing using the Analytical Hierarchy Process (AHP) method obtained the sequence results from each of the highest to lowest criteria and the highest weighted results were the quality criteria with the final weight value 0.71 after that followed the profit criteria with the final weight 0.29. After obtained the heightened criteria, the optimal alternative selected is Equipment with a weight value of 0.46, and followed by HR with a weight value of 0.38, then Infrastructure with a final weight value of 0.16.